Role of Antifreeze Glycoproteins (AFGPs) in Preventing Ice-formation - Professor Rosie Chu; Dr Victoria Garcia Sakai; Mr SHENGKAI ZHANG; Miss Jingjing Han; Mr Xudong Gu; Mr Zhixin Wang (ISIS Facility, 2019)
Antifreeze glycoproteins (AFGPs) are an important biological complex and a novel set of proteins that can prohibit the formation of ice. The AFGPs can be extracted from the blood plasma of Antarctic notothenioids and northern cod. The configuration change in amino acids or (sub-) domain inside a protein is often responsible for its activity, which is closely connected to the thermal hysteresis (TH) of AFGP, a unique characteristic of this family of protein. In this proposed research we are going to explore how AFGPs can prevent ice formation in D2O and H2O solutions by studying the dynamics of its hydration water and bulk water in the solution in the time range of several tens of picoseconds and up to few nm using QENS at IRIS.